PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA MELALUI METODE PEMBELAJARAN DEBAT AKTIF PADA MATA KULIAH KEWIRAUSAHAN - Wijaya, Shendy Andrie (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2019)
Based on the evaluation, learning in economics education courses still use that method one direction, in which the students listen, most of the students tend to be quiet, and students are rarely asked and expression. These conditions resulted in less active students and experiencing saturation in learning, so that will have an impact on student learning outcomes. To overcome these problems required the efforts of lecturers create attractive learning environment and has a learning innovation by involving students to acquire knowledge so as to facilitate the achievement of learning objectives in particular. Researchers attempting to implement a strategy of active learning (active learning) one debate active learning.Through active debate method (active debate) which is a blend of listening and speaking skills that can give freedom to all students to express their opinions in a way to think critically about an issue from all sides, according to ability and knowledge to be able to improve learning outcomes. Based on the results, it can be concluded that through active debate methods can enhance students' critical thinking skills in entrepreneurship courses. Such improvements can be seen from the average score of students' critical thinking students who obtained before any action is 1,9, then the cycle I got an average score of 2,8 and learning activities in the second cycle received an average score of learning activities amounting to 3,6. This means that the critical thinking skills of students in entrepreneurial learning criteria increased from low, to medium and increased again to high criteria.